Testing the Associations Between Adult Playfulness and Sensation Seeking: A SEM Analysis of Librarians and Police Officers - Brauer, Kay; Scherrer, Tiziana; Proyer, René T. (Frontiers in Psychology, 2021)
Playfulness is an understudied personality trait in adults. We examined the relationships between facets of adult playfulness and sensation seeking (SS) in distant vocational groups; namely, librarians (N = 339) and police officers (N = 399). First, manifest and latent group comparisons (measurement invariance analysis) showed that police officers were higher in SS than librarians, while we found no group differences for playfulness. Secondly, SEM analyses showed that playfulness was widely positively related to SS and findings were replicated across groups. However, the effects were of small to moderate size and playfulness and SS shared between 4 and 22% variance. Our findings indicate that playfulness is not redundant with SS. Our study extends the understanding of adult playfulness by clarifying its overlap and distinctiveness from SS.